Comparative study of TEC for GISTM stations in the Peninsular Malaysia region for the period of January 2011 to December 2012 - Mat Akir, Rohaida; Abdullah, Mardina; Chellapan, Kalaivani; Hasbi, Alina Marie; Bahari, Siti Aminah (American Scientific Publishers, 2017)
Total Electron Content (TEC) is a fundamental and the most prevalent parameter that affects Global Positioning System (GPS) signals, leading to delays, poor signals or total loss of signals. The gradients in TEC are frequently associated with disturbance in the ionosphere which explains the space weather behavior and indirectly causes inefficient operations of ground and space based Global Navigation Satellite System (GNSS) applications. The role of TEC variability is constructive in space weather prediction as it allows GNSS users to minimize rangerate errors in achieving highly reliable measurements. This paper therefore presents an analysis of the diurnal and seasonal activity dependence of TEC using data obtained from the GPS Ionospheric Scintillation and TEC Monitor (GISTM) at two stations in Peninsular Malaysia which are located at the Langkawi National Observatory, Langkawi, LGKW (06_19’N, 99_51’E) and Universiti Kebangsaan Malaysia, UKM (02_55’N, 101_46’E). Data for the two years (2011 and 2012), were recorded using the NovAtel GSV 4004B GISTM model equipment. Further investigations on a few more stations in the coast of Peninsular Malaysia will strengthen and consolidate the findings of this study.